Particle and Fibre Toxicology - Erdely, Aaron; Erdely, Aaron; Cassee, Flemming R.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Particle and Fibre Toxicology is a fully open access, peer-reviewed, online multi-disciplinary journal for new scientific data, hypotheses, and reviews on the toxicological effects of particles and fibres. The journal functions as a forum for scientific debate and communication among toxicologists as well as between scientists from other disciplines that produce and develop particle and fibre materials, including material sciences, biomaterials, and nanomedicine. Particle and Fibre Toxicology is a multi-disciplinary journal focused on understanding the physico-chemistry of particles, the possibilities for human exposure and biological outcomes, and regulatory issues in the workplace and general environment. In addition, there are diverse scenarios where particles may pose a toxicological threat due to new applications of old materials or introduction of new materials, which are readily welcomed by the journal. Particle and Fibre Toxicology provides a single, identifiable outlet for output from all these disciplines. Particle and Fibre Toxicology may also consider papers from the adjacent fields such as exposure sciences including dosimetry, biodistribution, and register-based epidemiological studies. Submission of experimental papers primarily dealing with omics data or single dose studies is not encouraged. Particles and fibres are toxicologically important in many scenarios, including exposure: during the manufacture or use of classical industrial products such as pigments and (vitreous) fibres; to particles from disturbing the earth's crust during mining and quarrying; from general anthropogenic sources in the environment such as PM10, cigarette smoke, biomass, and liquid fuel combustion; to nanomaterials that have been specifically engineered for special purposes, including for drug delivery and imaging. Please contact the Editor if you are in any doubt that the manuscript is in scope for Particle and Fibre Toxicology. If you wish to submit an epidemiological study, please contact us prior to submission with a submission enquiry (contact details below).
Keywords: Public health; Environmental health; Respiratory organs$1 (BDiseases.s; Toxicology; Nanotechnology; Occupational health services; Public Health; Environmental Health; Pneumology; Toxicology; Nanotechnology; Occupational Health